Ship and Offshore Structure Design in Climate Change Perspective. - Bitner-Gregersen, Elzbieta Maria. (SpringerBriefs in Climate Studies, 2013)
This inaugural volume on an emerging topic of vital interest details a risk-based approach to designing marine structures that accounts for unforeseen weather extremes caused by climate change, applying the principles to oil tanker designs of varying scale.